ASUHAN KEBIDANAN PADA IBU BERSALIN NY. S G3P2A0 USIA KEHAMILAN 38-39 MINGGU DENGAN RETENSIO PLASENTA DI RUMAH SAKIT AMELIA - Anis Setyowati (STIKES dan AKZI Karya Husada Kediri, 2023)
Postpartum hemorrhage is a condition where the amount of blood that comes out after giving birth either in the first 24 hours (primary) or more than 24 hours (secondary) after giving birth is more than 500cc. Bleeding that occurs within the first 24 hours after delivery is caused by tearing of the birth canal, uterine atony, retained placenta, retained placenta, and blood clotting disorders. Postpartum bleeding due to retained placenta is a condition where the placenta is stuck in the uterus and has not come out for 30 minutes after giving birth due to the uterus not contracting properly. The study aimed to provide midwifery care for women in the third stage of labor with retained placenta through a comprehensive approach to the management mindset of Varney's midwifery care. The method used is a case study to explore the problem. The research subject is Mrs. S G3P2A0 which was carried out in May 2022, in the delivery room of the Amelia Hospital. Data collection techniques include primary data including physical examination, interviews, observation, and secondary data, including documentation studies and literature studies. Data analysis was carried out by creating narratives from the results of interviews and examinations using Varney's 7 steps. Patients are observed and given care according to the authority of the midwife at the hospital which prioritizes collaborative care then independent care, and from the care provided the differences and gaps between theory and practice are discussed. This study concludes that there is no gap between theory and practice in midwifery care for Ms. S.